Perspectives of Linkage to Care Among People Diagnosed With HIV. (March 2015) - Cook, Christa L.; Lutz, Barbara J.; Young, Mary‐Ellen; Hall, Allyson; Stacciarini, Jeanne‐Marie
Abstract : N/A: Timely linkage to HIV care and treatment has led to improved individual and population benefits; however, 25%–31% of people diagnosed with HIV do not engage in care. Most linkage to care research has focused on larger metropolitan areas, but smaller metropolitan and rural areas encounter unique challenges to linkage to care. Our purpose was to examine factors influencing the decision to seek care by 27 people infected with HIV living in smaller metropolitan and rural areas of Florida. We used grounded theory methods to develop a theoretical model describing the decision‐making process and participant recommendations within the context of stigma. Participants described support, defining care, activating care, conflicting messages of care, and pivotal events influencing the care decision. Findings highlight the complexities of HIV care and suggest a client‐centered approach to address the multifaceted social and structural challenges people with HIV face in the journey from infection to care.